Suppression of the transforming growth factor-β signaling pathway produces a synergistic effect of combination therapy with programmed death receptor 1 blockade and radiofrequency ablation against hepatic carcinoma in mice. Issue 4 (1st April 2022) - Fan, Xiaoxiang; Gu, Lihu; Lv, Shuyi; Zhang, Meiwu; Zhuang, Luhui; Zhang, Yan; Chen, Ping
ABSTRACT: Primary liver cancer (PLC) significantly affects the health of patients globally owing to its high morbidity and low survival rate. Radiofrequency ablation (RFA) has recently been introduced for the clinical treatment of PLC. However, significant immunosuppressive effects are induced by RFA, which limits its application. This study aimed to explore the potential of combination therapy with RFA by investigating the effects of siRNAs against programmed death receptor 1 (PD-1) and transforming growth factor-β (TGF-β) on the antitumor effect induced by RFA. We observed that compared with si-NC, cell viability was reduced, apoptosis rate was elevated, release of inflammatory factors and percentage of CD3 + CD8 + cells were increased, and the PI3K/AKT/mTOR pathway was repressed in the co-culture of RFA-treated H22 cells and CD8 + T cells by transfection with si-PD-1 and si-TGF-β; these effects were further enhanced by co-transfection with si-PD-1 and si-TGF-β. Additionally, in H22 cell xenograft-bearing mice treated with RFA, compared with the si-NC group, repressed tumor growth, prolonged survival, increased production of inflammatory factors and expression of CD3 and CD8 in tumor tissues, and downregulation of the PI3K/AKT/mTOR pathway were observed in the si-PD-1 and si-TGF-β groups; these effects were further enhanced in the si-PD-1 + si-TGF-β group. Taken together, our data revealed that suppression of the TGF-β signaling pathway produced a synergistic antitumor effect of combination therapy with PD-1 blockade and RFA against PLC. uf0001